Adipose Stem Cell Secretome for Corneal Endothelial Regeneration: Ki-67 Expression, Hexagonality, and CV Restoration after Ultrasound Exposure in Phacoemulsification - Bakry, Mohammad Haikal; Primitasari, Yulia; Wahyuni, Indri; Komaratih, Evelyn; Sasono, Wimbo; Lestari, Pudji (Journal of Neonatal Surgery, 2025)
Corneal endothelial cell (CEC) damage, particularly following cataract surgery, remains a significant challenge in ophthalmology, as CECs have limited regenerative capacity. Adipose-derived stem cell (ASC) secretome, a rich mixture of cytokines, growth factors, exosomes, and non-coding RNAs, has shown promise in enhancing tissue repair and regeneration. Ki-67, a well-established marker of cell proliferation, serves as an indicator of the regenerative potential of CECs. Hexagonality, a measure of the uniform, regular cell shape crucial for maintaining the structural and functional integrity of the corneal endothelium. The coefficient of variation (CV) of endothelial cell size is a sensitive marker of endothelial dysfunction. The underlying mechanisms by which ASC secretome mediates these regenerative effects include the inhibition of oxidative stress, modulation of TGF-β signaling, and regulation of mitochondrial function. The secretome’s influence on mitochondrial integrity is particularly significant, as mitochondrial dysfunction is a key factor contributing to endothelial senescence and loss of function. Additionally, the paracrine signaling mediated by ASC exosomes plays a crucial role in enhancing cellular communication and tissue repair. This review discusses the clinical implications of ASC secretome in corneal endothelial regeneration and its potential as a non-invasive, donor-independent therapeutic option. By highlighting recent advancements and mechanisms, the review provides a comprehensive understanding of how ASC secretome could be utilized to address the challenges of corneal endothelial dysfunction, offering new prospects for treating endothelial cell loss and improving surgical outcomes in cataract patients